Academic grit and it’s impact on student learning in UiTM Sarawak Branch / Florence Sherrie Laney and Nurul Hafizah Zulkifli - Laney, Florence Sherrie; Zulkifli, Nurul Hafizah (2024)
Student learning is reflected in their academic achievement, which aims to bring about some changes in areas like knowledge, understanding, application, analytical power, synthesis, and evaluation. The purpose of this study is to investigate the academic grit on full time student learning in UiTM Sarawak Branch. This study will sample from around UiTM Sarawak Branch with a proposed sample size of 361 persons. The research data will be gathered using distribution of questionnaires will be send to full-time student of respondents. It is to determine the relationship between academic grit and student among male and female student in UiTM Sarawak Branch which are from Campus 1 & Campus 2.